Description of remote and contact personal connectors (Eurasian Journal of Learning and Academic Teaching, 2022)
The study of the phrase requires attention to the basic unit of the language - the word. Words can only express one meaning when they form a compound with another word, whether they are single-valued or multi-valued. The limited ability of a certain lexeme to form a compound in speech is explained by the originality of its lexical meaning, that is, according to the meaning of such a word, it can form a compound with very few words. By themselves, morphological means are also limitedly used in conjunction with such alexeme. The formation of a conjugation dictionary based on special conjunctions will contribute to the development of such areas as machine translation, computational  linguistics, and will become the linguistic basis of the national corpus of the Uzbek language.